Improving Endometrial Carcinoma Prognosis: A Case Report on Synergistic Moringa Treatment - Irfan, Noor ul ain; Saleem, Shemaila (Journal of Rawalpindi Medical College, 2025)
Endometrial adenocarcinoma is the most common gynecologic malignancy worldwide, particularly affecting postmenopausal women. While standard treatments include surgery, chemotherapy, and radiotherapy, there is growing interest in complementary therapies to improve prognosis. This case report presents a 62-year-old female diagnosed with stage II endometrial adenocarcinoma, who underwent standard chemotherapy and radiotherapy while incorporating Moringa Oleifera supplementation. Over six months, the patient demonstrated improved tolerance to treatment, reduced inflammation markers (CRP: 18 mg/L to 5 mg/L), and enhanced immune function (increase in CD4+/CD8+ ratio). Tumor regression was confirmed via imaging, showing a 40% reduction in lesion size post-treatment. The patient also reported improved energy levels and reduced chemotherapy-related side effects. This case highlights the potential of Moringa Oleifera as a synergistic adjunct to conventional therapy in endometrial carcinoma. Further clinical studies are needed to validate these findings.